1999
DOI: 10.1076/jcen.21.5.701.868
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Wisconsin Card Sorting Test in the Detection of Malingering in Student Simulator and Patient Samples

Abstract: We analyzed the ability of the Wisconsin Card Sorting Test to distinguish between 41 malingering and 31 normal undergraduates, and 17 probable malingering and 16 brain injured patients. A logistic regression consisting of number of categories (CAT) and failure to maintain set (FMS) distinguished malingering and normal undergraduates with 70.7% sensitivity, 87.1% specificity, and 77.8% overall classification, and distinguished patients suspected of malingering from brain injured controls with 82.4% sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…High FMS has been observed in patients with known or suspected orbitofrontal pathology [13] and, thus, may be a negative outcome indicator similar to the presence of anosmia [16]. Further, this study indicates that high FMS does reflect a valid WCST profile and is not indicative of poor motivation or malingering, as has been argued [17]. Cluster 2 was characterized by poor problem-solving, which could indicate the need for a special focus on problem-solving, hypothesis testing and critical/flexible thinking during rehabilitation.…”
Section: Discussionsupporting
confidence: 47%
“…High FMS has been observed in patients with known or suspected orbitofrontal pathology [13] and, thus, may be a negative outcome indicator similar to the presence of anosmia [16]. Further, this study indicates that high FMS does reflect a valid WCST profile and is not indicative of poor motivation or malingering, as has been argued [17]. Cluster 2 was characterized by poor problem-solving, which could indicate the need for a special focus on problem-solving, hypothesis testing and critical/flexible thinking during rehabilitation.…”
Section: Discussionsupporting
confidence: 47%
“…However, effort during testing has a direct impact on WCST performance (Bernard, McGrath, & Houston, 1996;Greve, Bianchini, Mathias, Houston, & Crouch, 2002a;Greve, Heinly, Bianchini, & Love, 2009;King et al, 2002;Suhr & Boyer, 1999) and should be considered as a possible explanation for observed impairments. Binder, Kelly, Villanueva, and Winslow (2003) reported that mild TBI had no significant impact on WCST perseverative responses when motivation during testing was controlled for using a measure of cognitive performance validity.…”
mentioning
confidence: 96%
“…Against the Suhr and Boyer (1999) equation, all CIM cutoffs cleared the lower threshold for specificity. The ≤9 raw score cutoff had .36 sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…To maximize the purity of the reference groups used to calibrate the target PVT, Borderline cases were excluded from (Heinly et al, 2005;Spencer et al, 2013); LM Logical Memory (Bortnik et al, 2010;Pearson, 2009), CVLT-II recognition hits (RH CVLT-II ; Wolfe et al, 2010), and Forced Choice Recognition (FCR CVLT-II ; Moore & Donders, 2004;Bauer et al, 2005) cross-validation analyses, following recommendations by Greve and Bianchini (2004). Finally, the logistical regression equations developed by Suhr and Boyer (1999) and King et al (2002) were used as alternative reference PVTs. They were selected because they are based on WCST variables that are not verbally mediated (like the EI-5) or recognition based (like the TOMM).…”
Section: Methodsmentioning
confidence: 99%